Evaluasi kepuasan wisatawan pada destinasi Argowisata Panyaweuyan - Sri Umyati; Sri Ayu Andayani; Dinar; Aaz Azamudin Tifani (Fakultas Pertanian Universitas Majalengka, 2025)
The Panyaweuyan terraced area is a tourist area that has local wisdom values from farming culture in the area. These local wisdom values attract tourists to visit, starting from just enjoying its beauty, educational tours and even historical tours of farming culture. Seeing the above phenomenon, it is necessary to direct this research to measure the satisfaction of visitors to Panyaweuyan agrotourism and its impact on the development of Panyaweuyan agrotourism itself. The aim of this research is to identify visitor satisfaction and its impact on the development of Panyaweuyan agrotourism. The research method used in this research is a survey method and the selection of research locations was carried out purposively. Respondents were determined using an accidental sampling technique with a limit of 60 visitors. Meanwhile, this research technique uses IPA and CSI analysis techniques to determine visitor satisfaction with a descriptive approach. This is done by describing, identifying and interpreting something that exists or is happening and being experienced in the research object to determine its impact on the development of Panyaweuyan agrotourism. The research results show that by carrying out CSI analysis, tourists are satisfied with what Panyaweuyan agrotourism offers (scenery, services, and facilities) with a satisfaction level of 74.95%. Meanwhile, the results of the IPA analysis show that there are still many things that are priorities for improving agrotourism, three of which are natural scenery, tourism service procedures and the benefits felt by visitors.